Behavioural and biochemical responses to methamphetamine are differentially regulated by mGlu2 and mGlu3 metabotropic glutamate receptors in male mice. (15th September 2021) - Busceti, Carla L.; Ginerete, Roxana P.; Di Menna, Luisa; D'Errico, Giovanna; Cisani, Francesca; Di Pietro, Paola; Imbriglio, Tiziana; Bruno, Valeria; Battaglia, Giuseppe; Fornai, Francesco; Monn, James A.; Pittaluga, Anna; et al.
Abstract: Group II metabotropic glutamate receptors (mGlu2 and mGlu3 receptors) shape mechanisms of methamphetamine addiction, but the individual role played by the two subtypes is unclear. We measured methamphetamine-induced conditioned place preference (CPP) and motor responses to single or repeated injections of methamphetamine in wild-type, mGlu2 −/−, and mGlu3 −/− mice. Only mGlu3 −/− mice showed methamphetamine preference in the CPP test. Motor response to the first methamphetamine injection was dramatically reduced in mGlu2 −/− mice, unless these mice were treated with the mGlu5 receptor antagonist, MTEP. In contrast, methamphetamine-induced sensitization was increased in mGlu3 −/− mice compared to wild-type mice. Only mGlu3 −/− mice sensitized to methamphetamine showed increases in phospho-ERK1/2 levels in the nucleus accumbens (NAc) and free radical formation in the NAc and medial prefrontal cortex. These changes were not detected in mGlu2 −/− mice. We also measured a series of biochemical parameters related to the mechanism of action of methamphetamine in naïve mice to disclose the nature of the differential behavioural responses of the three genotypes. We found a reduced expression and activity of dopamine transporter (DAT) and vesicular monoamine transporter-2 in the NAc and striatum of mGlu2 −/− and mGlu3 −/− mice, whereas expression of the DAT adaptor, syntaxin 1A, was selectively increased in the striatum of mGlu3 −/− mice. Methamphetamine-stimulated dopamine release in striatal slices was largely reduced in mGlu2 −/−, but not in mGlu3 −/−, mice. These findings suggest that drugs that selectively enhance mGlu3 receptor activity or negatively modulate mGlu2 receptors might be beneficial in the treatment of methamphetamine addiction and associated brain damage. Graphical abstract: Image 1 Highlights: Our aim was to dissect the role of mGlu2 and -3 receptors in methamphetamine addiction. Responses to methamphetamine were blunted in mice lacking mGlu2 receptors. Methamphetamine sensitization was amplified in mice lacking mGlu3 receptors. Methamphetamine toxicity was also amplified in mice lacking mGlu3 receptors. Selective mGlu2 and mGlu3 ligands are drug candidates in methamphetamine addiction.